A Novel Experimental Design Method to Optimize Hydrophilic Matrix Formulations with Drug Release Profiles and Mechanical Properties. Issue 10 (23rd July 2014) - Choi, Du Hyung; Lim, Jun Yeul; Shin, Sangmun; Choi, Won Jun; Jeong, Seong Hoon; Lee, Sangkil
<x xml:space="preserve">Abstract</x> To investigate the effects of hydrophilic polymers on the matrix system, an experimental design method was developed to integrate response surface methodology and the time series modeling. Moreover, the relationships among polymers on the matrix system were studied with the evaluation of physical properties including water uptake, mass loss, diffusion, and gelling index. A mixture simplex lattice design was proposed while considering eight input control factors: Polyethylene glycol 6000 (x1), polyethylene oxide (PEO) N‐10 (x2), PEO 301 (x3), PEO coagulant (x4), PEO 303 (x5), hydroxypropyl methylcellulose (HPMC) 100SR (x6), HPMC 4000SR (x7), and HPMC 105SR (x8). With the modeling, optimal formulations were obtained depending on the four types of targets. The optimal formulations showed the four significant factors (x1, x2, x3, and x8) and other four input factors (x4, x5, x6, and x7) were not significant based on drug release profiles. Moreover, the optimization results were analyzed with estimated values, targets values, absolute biases, and relative biases based on observed times for the drug release rates with four different targets. The result showed that optimal solutions and target values had consistent patterns with small biases. On the basis of the physical properties of the optimal solutions, the type and ratio of the hydrophilic polymer and the relationships between polymers significantly influenced the physical properties of the system and drug release. This experimental design method is very useful in formulating a matrix system with optimal drug release. Moreover, it can distinctly confirm the relationships between excipients and the effects on the system with extensive and intensive evaluations. © 2014 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 103:3083–3094, 2014